2012
DOI: 10.1021/jf301807g
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, Natural Sources, Dietary Intake, Pharmacokinetic Properties, and Biological Activities of Hydroxycinnamic Acids

Abstract: Hydroxycinnamic acids are the most widely distributed phenolic acids in plants. Broadly speaking, they can be defined as compounds derived from cinnamic acid. They are present at high concentrations in many food products, including fruits, vegetables, tea, cocoa, and wine. A diet rich in hydroxycinnamic acids is thought to be associated with beneficial health effects such as a reduced risk of cardiovascular disease. The impact of hydroxycinnamic acids on health depends on their intake and pharmacokinetic prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
306
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(315 citation statements)
references
References 251 publications
3
306
0
6
Order By: Relevance
“…Because of, for instance, beneficial anticancer effects, Nichenametla et al (2006), antiinflammatory potential, Pragasam et al (2013) potential beneficial effects in treating metabolic disorders, Yoon et al (2013), antibacterial effects, Lou et al (2012) and a possible preventive effect on myocardial infarct size, Roy et al (2013) of p-coumaric acid, or the beneficial effects of caffeic acid, El Seedi et al (2012), Vauzour et al (2010), da Cunha et al (2004, these and other "minor" phenolics should be an inevitable part in the new labeling framework.…”
Section: Ripening Indexmentioning
confidence: 99%
“…Because of, for instance, beneficial anticancer effects, Nichenametla et al (2006), antiinflammatory potential, Pragasam et al (2013) potential beneficial effects in treating metabolic disorders, Yoon et al (2013), antibacterial effects, Lou et al (2012) and a possible preventive effect on myocardial infarct size, Roy et al (2013) of p-coumaric acid, or the beneficial effects of caffeic acid, El Seedi et al (2012), Vauzour et al (2010), da Cunha et al (2004, these and other "minor" phenolics should be an inevitable part in the new labeling framework.…”
Section: Ripening Indexmentioning
confidence: 99%
“…Financially viable directions for cereal-based biorefineries would therefore embrace a reorientation in the current cereal processing methodologies by implementing parallel production lines for the efficient exploitation of cereal processing wastes [3]. One of the most versatile classes of substances that occur in abundant industrial cereal solid wastes (ICSWs), such as brans, is polyphenols which are secondary plant metabolites with potential health benefits, attributed to their antioxidant activity, but also their antimicrobial, antiviral, and anti-inflammatory effects [4,5]. Hence, ICSWs may be considered as a low-cost resource for the metabolites with potential health benefits, attributed to their antioxidant activity, but also their antimicrobial, antiviral, and anti-inflammatory effects [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most versatile classes of substances that occur in abundant industrial cereal solid wastes (ICSWs), such as brans, is polyphenols which are secondary plant metabolites with potential health benefits, attributed to their antioxidant activity, but also their antimicrobial, antiviral, and anti-inflammatory effects [4,5]. Hence, ICSWs may be considered as a low-cost resource for the metabolites with potential health benefits, attributed to their antioxidant activity, but also their antimicrobial, antiviral, and anti-inflammatory effects [4,5]. Hence, ICSWs may be considered as a low-cost resource for the recovery of phytochemicals, which may have a significant prospect as pharmaceuticals, cosmetic constituents, food additives and nutritional supplements.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Yuan et al have shown that PA can be incorporated into plasma and erythrocytes and a part of PA can also be metabolized into cis 9, trans 11-18:2 in humans. The mechanism of in vivo transformation of PA into cis 9, trans 11-18:2 is not precisely known [16][17][18][19][20] .…”
Section: Review Articlementioning
confidence: 99%